Bio-Inspired Rotor Design Characterization of a Horizontal Axis Wind Turbine - J. Gaitan-Aroca; Fabio Sierra; Jose Ulises Castellanos Contreras (Energies, 2020)
In this paper, the performance of a biomimetic wind rotor design inspired by Petrea Volubilis seed is presented. Experimentation for this rotor is configured as a horizontal axis wind turbine (HAWT) and numerical analysis is done in order to obtain performance curves with the open-source computational fluid dynamics (CFD) software OpenFoam®. Numerical analysis and experimental results are compared for power Coefficient (Cp) and thrust coefficient (CT). The biomimetic rotor analysis is also compared with experimental results exposed by Castañeda et al. (2011), who were the first to develop those experimentations with this new rotor design. Computational fluid dynamics simulations were performed using an incompressible large Edyy simulation (LES) turbulence models with a localized sub-grid scale (SGS) dynamic one-equation eddy-viscosity. A dynamic mesh based on an arbitrary mesh interface (AMI) was used to simulate rotation and to evaluate flow around rotor blades in order to accurately capture the flow field behavior and to obtain global variables that allow to determine the power potential of this wind rotor turbine. This study will show the potential of this new rotor design for wind power generation.